Comparative assessment of periodontal tissue condition during prosthetics with different types of inserts for aesthetic crowns - L. Chulak; S. Nebogatov; P. Maksymenko (Kazimierz Wielki University, 2022)
The advantages of the restoration of chewing teeth with ceramic inlays and composite materials are determined by the favorable physical and mechanical properties of modern ceramics with zero water absorption, optimal coefficient of thermal expansion, low thermal conductivity, biological compatibility and chemical stability in the oral cavity.. It is ceramics that is considered the most chemically inert material, and even the components - wear products that appear during abrasion do not cause allergic or toxic reactions in the oral cavity or inflammation of the marginal gums. The aim of the study was to assess the state of the periodontal tissues of teeth restored with different types of inlay core and, thus, to predict the development of pathological processes in the tissues surrounding the restored root. The conducted clinical and laboratory studies showed the significant advantages of the method of manufacturing a hip insert made of ceramics developed by us. Thus, according to the results of a comparative study of the dynamics of the level of glycogen in the periodontal tissues of the roots of teeth restored under aesthetic crowns with the use of root tabs, it is obvious that the use of ceramic tabs during prosthetics with ceramic crowns does not cause inflammatory processes in the periodontal tissues, but after traumatic exposure by preparation and preparation of the tooth before prosthetics, recover quite quickly to the level of the indicator at the healthy gingival margin.